Productivity Evaluation of Digging, Loading, and Hauling Equipment in Limestone Mining, PT Pertama Mina Sutra Perkasa, Jember, Indonesia - Santoso, Raffaello; Suparno, Fanteri Aji Dharma; Irawan, Januar Fery (Lembaga Penelititan dan Pengabdian kepada Masyarakat - Institut Teknologi Adhi Tama Suraba, 2024)
The failure of meeting the productivity target often occurs in mining operations and is caused by several technical obstacles. PT Pertama Mina Sutra Perkasa set a productivity target of 80 tons/hour for loading and digging equipment and 35 tons/hour for transportation equipment. An analysis of factors that affect productivity needs to be studied in order to find out the causes of not achieving the productivity targets set by the company. This research was conducted on the limestone quarry of PT Pertama Mina Sutra Perkasa (PMSP) located in Grenden Village, Puger District, Jember Regency using quantitative research methods. Research begins with the formulation of problems and then data collection and processing. Data that has been processed and analyzed can then be the basis for determining efforts to improve the productivity of loading and transporting excavations. There are three loadings location not reached the productivity target. Not achieving tool productivity targets due to low work efficiency, suboptimal tool distribution time, and a combination of a less than ideal number of tools. In this study, productivity improvement was carried out by reducing the actual obstacle time in order to increase effective working time and tool efficiency.